Quartz surface morphology of Tertiary rocks from North East Sarawak, Malaysia: Implications for paleo-depositional environment and reservoir rock quality predictions - Ali, A.M. (Elsevier, 2014)
The relationship between quartz surface textural defects (derived from weathering and diagenesis), palaeo-depositional environment and reservoir quality were studied using Tertiary outcrop rock samples obtained from the Belait and Lambir formations of the Sarawak Basin, Malaysia. Thin sections were used for mineral identification and to make observations regarding grain size and texture. Morphological characterization of the samples was performed using scanning electron microscopy (SEM) attached with energy-dispersive X-ray spectrometry (EDX) system, to show variations in quartz surface texture. The SEM images of Belait conglomerates reveal euhedral quartz crystals characterized with prominent mechanical weathering defects (such as straight and conchoidal fractures and striations). Conversely, the analysis of the Lambir sandstones identified chemical weathering features (such as chemical etchings, pitting, solution pits and notches). On the basis of petrology, SEM and CT scan images, evaluation results of reservoir quality indicate that the Lambir Formation in this study area is high-energy coast deposit, with apparent tide-dominated features; while Belait Formation is neritic-delta deposit, with obvious wave-dominated features; reservoir quality of the Belait Formation and Lambir Formation are poor, but the porosity of the Belait Formation is relatively higher than that of the Lambir Formation. Â© 2014 Research Institute of Petroleum Exploration & Development, PetroChina.